SPESIES HAMA INVASIF Leptocybe invasa FISHER & LA SALLE DAN Ophelimus maskelli (ASMEAD) DAN UPAYA PENGENDALIANNYA PADA TEGAKAN AMPUPU DI PULAU TIMOR - Iburuni, Johanes Umbu Rebu; Cakswindryandani, Ni Luh Putu Ravi; Nalle, Ryan P I (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Ampupu (Eucalyptus urophylla S.T Blake) is a key component of the semi-arid savanna forest found abundantly in East Nusa Tenggara (NTT). The purpose of this article is to explore the potential of invasive pests, Leptocybe invasa Fisher & La Salle and Ophemelinus maskelli (Asmead) as well as the available control efforts based on limited journal literature. Currently, Leptocybe invasa and Ophelimus maskelli are significant pests affecting eucalyptus plants. Control efforts can be implemented by harnessing the potential of natural enemies, such as parasitoids, and enforcing quarantine measures in regions where Eucalyptus spp. is distributed. Keywords : Ampupu, Leptocybe invasa, Ophemelinus maskelli , eucalyptus